Espalhamento elástico de elétrons e ionização dissociativa da molécula de trimetil fosfato - Pilla Bardela, Fernanda (2021)
The trimethyl phosphate molecule is an important prototype for studying electron interactions with molecules of biological significance containing the phosphate group. These studies contribute to the understanding of energy transfer processes in living organisms and have an application in radiotherapy and radio-diagnostic techniques development. In this context, we present an experimental and theoretical study on the interaction of electrons with this molecule. Experimentally, elastic differential cross sections data were obtained in the energy range from 5 to 800 eV within the angular range from 10◦ to 130◦ using the relative flow technique. Momentum transfer cross sections were determined by the integration of differential cross sections in the same energy range. Experimental data for the dissociative ionization pattern in the region extending from the ionization threshold to 1000 eV were also obtained. Theoretically, elastic differential cross sections and total ionization cross sections were calculated using the independent atom model and the binary-encounter Bethe model, respectively. For the latter, different density functionals were investigated. The experimental and theoretical results were compared with the literature for trimethyl phosphate and other molecules of the same category of phosphate esters. In overall, a good agreement is observed. The elastic cross sections data have recently been published [F. P. Bardela et al., Elastic electron collisions with trimethyl phosphate, J. Phys. B: At. Mol. Opt. Phys. 54 075203 (2021)].